The duties of the almoner (memorandum) - Mudd, Edith E.
1901-10-25 1901 1900s 5 pages judging the efficiency of the treatment, coupled with waste of Hospital Drugs or appliances. Class III. The possibility of abuse or waste in allowing Patients to attend the Out Patients' Department where the treatment is limited, and should be supplemented by further help in nourishment or altogether different conditions for cure. Let me take first Class I., via: The Ineligible. I have been led to believe it is considered that too much of the Almoner's time is given to Relief Work, to the negligence of the primary reason for the institution of her office, i.e., Enquiry Work. I emphatically state that no one, single-handed, could hope to see all the new Patients. If they did they would defeat their own ends, viz., send away many who could not afford to pay and pass many who could. For example one woman will tell you her husband earns 50/- a week and it is only after some minutes you find he has been unable to work for three months. Or the other hand, nearly all are out of work when they come to the Hospital; but you will probably find out that they left work yesterday, which may have been Friday, and return to it on Monday. Anyone who has had any experience of the class of applicant who attends an Out Patients' Department knows it takes a considerable time to sort the information they may or may not be willing to give, as the case may be. I have always the consciousness of doing inefficient work if I rush through cases, or take over a limited number and this is the conclusion accepted by all who do Enquiry Work. This I think would soon be apparent to anyone interested enough to listen to cases being taken down. As regards the Enquiry Work pure and simple, I am handicapped in many ways and not by any means always by the needs 378/IMSW/A/1/4/3a